ROMANTISME MELANKOLIS PUISI AL-MASA’ KARYA KHALIL MUTHRAN (Aliran Romantisme dalam Sastra Arab) - ulil abshor; hanim mawarida (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2022)
This study discusses the field of romanticism, especially analyzing literary the literature work with the theory of romanticism characterized by melancholy (moodiness) against one of the poem belong to a famous romanticism school figure, Khalil Muthran, entitled al-Masa (twilight). The purpose of this study is to find out the study of the field of romanticism, along with its characteristic, and to explore the romantic figure named Khalil Muthran and the application of the theory of melancholy Romanticism (moodiness) to his poem entitled al-Masa. This study used descriptive qualitative method. The technique used is the listening and note-taking technique. The results obtained are that it has been found that there is a match between the theory of the characteristics of the flow of romanticism and its application to al-Masa' poetry, that the poem contains elements of romance, namely there are various characteristics of romance such as nature, melancholy, primitivism, sentimentalism, individualism and exoticism. However, the researcher focuses more on analyzing the flow of melancholic romanticism, so the findings that can be described are the discovery of about 10 stanzas of poetry that are included in the melancholic romance category.